Retrospective study outcome of term breech delivery in Hospital Sultan Ismail Johor Bahru - Rambat, Norazayati (2015)

(untitled)
Objective : To evaluate the maternal and perinatal morbidity and mortality in caesarean delivery group and vaginal delivery group of breech presentation at term. Method : We restrospectively reviewed all breech presentation completed 37 weeks from September 2012 until January 2014 using birth registry book and HSIAPPS computer system.. The details included the antenatal review, intrapartum events, immediate postpartum event and neonatal outcome. Patient was contacted via phone to enquire about the postpartum complication. Results: A total of 160 patient were recruited in this study. 83 patients (51.9%) underwent caesarean section and 77 patient successfully had vaginal delivery (48.1%). One patient (1.3%) from vaginal delivery developed episiotomy wound breakdown. No postpartum hemorrhage observed in vaginal delivery. Two patients (2.4%) in caesarean section group had primary postpartum hemorrhage and required blood transfusion. No endometritis, postpartum pyrexia and maternal mortality seen. The maternal complication was not significant for both group. There was no significance different between the Apgar Score (AS) at 5 and 10 minutes for both group (p>0.05). 2 babies (16.7%) from vaginal delivery developed skin laceration at genital area, however there was no neonatal complication such as head entrapment, limbs fracture, skull fracture, and internal organ injury in both groups. No neonatal mortality seen in this study. Conclusion : There was no significant maternal and neonatal mortality and morbidity 8 observed in this study.